2020
DOI: 10.1001/jama.2020.19395
|View full text |Cite
|
Sign up to set email alerts
|

Neurodevelopmental Outcomes at Age 5 Years After Prophylactic Early High-Dose Recombinant Human Erythropoietin for Neuroprotection in Very Preterm Infants

Abstract: rapid-exercise-tests-for-exertional-desaturation-in-covid-19/ 6. Rodríguez-Molinero A, Narvaiza L, Ruiz J, Gálvez-Barrón C. Normal respiratory rate and peripheral blood oxygen saturation in the elderly population.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
15
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 23 publications
(19 citation statements)
references
References 6 publications
(11 reference statements)
1
15
0
Order By: Relevance
“…However, more recently, a randomized, double-blind trial of high-dose rEpo administered to extremely preterm infants from 24 h after birth until 32 weeks post menstrual age, had no effect on the risk of severe neurodevelopmental impairment or death at 2 years of age [ 71 ]. Further, a similar study of 448 infants randomized to receive repeated doses of rEpo started within 3 h of very preterm birth found no effect on neurodevelopmental outcomes at 2 and 5 years of age [ 72 , 73 ]. It is possible that the relatively delayed start (within 24 h) and infrequent dosing regimen in Juul et al [ 71 ] may have contributed to the lack of neuroprotection seen in this study as infants received 1000 IU/Kg rEpo every 48 h for a total of 6 doses followed by 400 IU/Kg 3 times per week, whereas the study in preterm fetal sheep showing partial neuroprotection used early initiation of treatment at 30 min and a prolonged infusion to maintain a stable plasma rEpo concentration [ 118 ].…”
Section: Potential Neuroprotective Treatments That Have Been Invesmentioning
confidence: 99%
“…However, more recently, a randomized, double-blind trial of high-dose rEpo administered to extremely preterm infants from 24 h after birth until 32 weeks post menstrual age, had no effect on the risk of severe neurodevelopmental impairment or death at 2 years of age [ 71 ]. Further, a similar study of 448 infants randomized to receive repeated doses of rEpo started within 3 h of very preterm birth found no effect on neurodevelopmental outcomes at 2 and 5 years of age [ 72 , 73 ]. It is possible that the relatively delayed start (within 24 h) and infrequent dosing regimen in Juul et al [ 71 ] may have contributed to the lack of neuroprotection seen in this study as infants received 1000 IU/Kg rEpo every 48 h for a total of 6 doses followed by 400 IU/Kg 3 times per week, whereas the study in preterm fetal sheep showing partial neuroprotection used early initiation of treatment at 30 min and a prolonged infusion to maintain a stable plasma rEpo concentration [ 118 ].…”
Section: Potential Neuroprotective Treatments That Have Been Invesmentioning
confidence: 99%
“…There were no beneficial effects on any secondary outcomes. While significantly improved neurodevelopment at the age of 3.5 to 4 years has been reported in one RCT ( 11 ), prophylactic high-dose rhEPO had no effect on cognitive scores at 5 years of age in a large Swiss RCT ( 12 ).…”
Section: Discussionmentioning
confidence: 87%
“…Studies have shown that DR occurs in both type 1 diabetes and type 2 diabetes[ 41 ]. With the increase in the number of diabetic patients, DR has become the main cause of visual impairment in diabetic patients[ 42 ]. The whole pathological process of DR includes important pathological changes such as loss of retinal capillary pericytes, thickening of basement membrane, loss of endothelial barrier function, destruction of blood-retinal barrier, and lead to retinal ischemia, which will increase the level of VEGF.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, a change in EPO expression is considered as an important factor affecting the retinopathy of prematurity. EPO treatment can effectively protect the nervous system and optic nerve development of premature infants[ 42 , 43 ]. HIF-1α is stably expressed under hypoxia; it can regulate EPO and VEGF expression and promote RNV[ 44 , 45 ].…”
Section: Discussionmentioning
confidence: 99%